Variables that affect educational quality in a context of health crisis in public educational institutions in Comas - Menacho-Vargas, Isabel (2021)
Quantitative study, basic type, cross-sectional correlations -causal design, describes relationships between two independent variables, knowledge management and pedagogical leadership, and the dependent variable educational quality.It has an explanatory level and a synthesis of the theoretical contributions has been made. The instruments were applied to 112 teachers from a population of 181 teachers, the reason was that the Google form was used through a link that was sent to the teachers in order to access the surveys. The instruments were 3 surveys on educational quality, knowledge management and pedagogical leadership. The same ones that have content validity, for which the expert judgment technique was used, the same ones who have considered that the instruments were applicable. In addition, the reliability of the instruments was obtained, through Cronbach's Alpha, in educational quality with 22 items, a coefficient of .928. Knowledge management with 22 items and a coefficient of .930 and in pedagogical leadership of 20 items with .914, of reliability coefficient. The results find a chi square of 17.311 and p value of significance of 0.002, which is in the allowed values, lower than 0.05, therefore, it is demonstrated that knowledge management and pedagogical leadership affects educational quality in a context of health crisis in educational institutions in the district of Comas.